Adaptação e serviços de polinização de Melipona quadrifas- ciata Lepeletier, 1836 (Hymenoptera, Meliponina) em cultivo fechado de Lycopersicon esculentum Mill. (Solanaceae) - Bartelli, Bruno Ferreira (2013)
Studies involving the management of pollinators in greenhouses have indicated an improvement in productivity and fruit quality. The stingless bees are considered the most promising in use as commercial pollinators. However, the knowledge about management techniques of these bees in greenhouses is still scarce. This study aimed to evaluate the adaptation and efficiency of pollination of Melipona quadrifasciata in greenhouses of Lycopersicon esculentum, sweet grape variety, as well as analyze the floral biology of this plant species. The study was conducted in two greenhouses located in Araguari-MG, Brazil. In one, we used only the mechanical method of pollination and, in the other, pollination by mechanical method was associated with pollination performed by bees by the introduction of six nests of M. quadrifasciata. The development of the colonies inside the greenhouse was investigated and the foraging behavior of workers was assessed before introduction, into the greenhouse and after the nests had been removed. The productivity of the greenhouses was compared and quality of tomatoes was evaluated by size, weight, number of seeds and total sugar content. With confinement, the daily period of foraging decreased and bees started collecting pollen in flowers after approximately six months. Tomatoes originated from flowers visited by workers of M. quadrifasciata produced about 47% more seeds and were approximately 14% more concentrated in sugars. These results suggest that the use of M. quadrifasciata for pollination of tomato shows promise, since positive effects were generated on fruit quality. However, the diffusion of sunlight and blocking of ultraviolet radiation caused by the cover of the greenhouse hinder orientation and identification of flowers by workers. Structural changes in the greenhouses, as well as the improvement of management techniques are required for better utilization of stingless bees in the pollination of plant species grown in greenhouses.